Feminism(s) & NGO leadership in emergent societies - Mendes, Constança Silveira Corrêa (2018)
Purpose – This work aims to identify how different perspectives of Feminism influence the leadership practices of an NGO from Latin America. In the course of this work, determinants of feminisms are analyzed and implications for the NGO leadership are drawn. Design/Methodology – The research relies on primary data collected through interviews with three people that have a close relationship with the organization. To draw valid conclusions, the data was analyzed using a protocol framework. Findings – The presence of different perspectives of feminisms that co-exist in harmony can be a main factor to prepare the organization’s leader to deal with complex situations. Using a strategy of both/and leadership leads to effective and successful organizational outcomes. Research limitations – This work focused on an NGO located in Brazil, more specifically in Rio de Janeiro. NGOs from other locations were not covered by the data, therefore no general conclusions on the leadership of NGOs from other places can be drawn. Practical implications – This research can help organizations in the business world to understand the importance of feminisms and how being able to respond to paradoxes can lead to effective and successful organizational outcomes. Originality – To the knowledge of the author, this is the first study that combines the topics of Feminism with the leadership of NGOs, to better understand the relationship between them.